Diagnostic impact of additional O-(2-[18F]fluoroethyl)-L-tyrosine (18F-FET) PET following immunotherapy with dendritic cell vaccination in glioblastoma patients. (2nd November 2021) - Kristin Schmitz, Ann; Sorg, Rüdiger V.; Stoffels, Gabriele; Grauer, Oliver M.; Galldiks, Norbert; Steiger, Hans-Jakob; Kamp, Marcel A.; Langen, Karl-Josef; Sabel, Michael; Rapp, Marion
Abstract: Objective: Vaccination therapy using tumour antigen-loaded, autologous dendritic cells (DC) is a promising therapeutic approach alongside standard treatment for glioblastoma (GBM). However, reliable diagnostic criteria regarding therapy monitoring are not established. Here, we analysed the impact of additional 18 F-fluoroethyl-tyrosine positron emission tomography ( 18 F-FET PET) imaging following DC vaccination therapy. Methods: We analysed data of GBM patients who received DC vaccination therapy. Following MRI diagnosis of tumour recurrence, additional static and dynamic 18 F-FET PET imaging was performed. Vaccination was performed five times by intradermal injections, either weekly between concomitant radio/-chemotherapy and intermittent chemotherapy or after tumour recurrence, before re-radiation therapy. MRI and 18 F-FET PET results were compared and correlated with clinical data. Results: Between 2003 and 2016, 5 patients were identified who received DC vaccination and 18 F-FET PET imaging (1 female/4 males; mean age: 44 ± 14 y). 3/5 patients showed congruent results of tumour progression. In three patients 18 F-FET PET indicated treatment related changes, which was in contrast to MRI findings that indicated tumour progression. In these patients 18 F-FET PET results could be confirmed by either neuropathological diagnosis or according to the RANO criteria Conclusions: Despite the small patients number our results indicate an additional impact of 18 F-FET PET for monitoring outcome following vaccination therapy.